2013
DOI: 10.5812/ircmj.8986
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Breathing Exercises on the Nocturnal Enuresis in the Children with the Sleep-Disordered Breathing

Abstract: BackgroundThe nocturnal enuresis is one of the most common complaints of childhood. Upper airway obstruction and nocturnal snoring affect the nocturnal enuresis in children.ObjectivesThe aim of this study was to investigate the effects of breathing exercises on the nocturnal enuresis in the children with the sleep-disordered breathing.Patients and MethodsThis study was conducted in year of 2011 by a semi-experimental design with the control group among 40 children, aged 6 - 12 years, who had the nocturnal enur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Chiropractic can be effective at restoring bladder control by correcting structural deviations and misalignment (5). Breathing exercises in enuretic children with sleep-disordered breathing, cause a better response to antidiuretic hormone and better control of bladder muscles by increasing the oxygen level (26). The exact mechanism for hyp-nosis effectiveness in improving NE is unknown and it seems to work by its own specific rationales in enuresis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chiropractic can be effective at restoring bladder control by correcting structural deviations and misalignment (5). Breathing exercises in enuretic children with sleep-disordered breathing, cause a better response to antidiuretic hormone and better control of bladder muscles by increasing the oxygen level (26). The exact mechanism for hyp-nosis effectiveness in improving NE is unknown and it seems to work by its own specific rationales in enuresis.…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that the frequency of breathing exercises reduce the nocturnal enuresis episodes in enuretic children with abnormal breathing pattern. Thus, this method can be used as a simple method with low cost and is more efficient than other approaches (26).…”
Section: Exercise Therapymentioning
confidence: 97%
“…When the diaphragm is not properly engaged, diaphragmatic excursion is less [ 81 ]. When the amplitude of diaphragm movement is compromised, there is a subsequent reduction in lung volume [ 82 ]. When lung volume decreases, the throat collapses more easily.…”
Section: Applying the Three Dimensions Of Breathing Re-education Tmentioning
confidence: 99%
“…Overall, 15% to 30% of children older than six years of age, 15% of children with five years of age, 7% of children with eight years of age, and 1% of children with 15 years of age, wet their bed at least one night per month; the odds ratio of nocturnal enuresis is 1.4:1 in males and females (5)(6)(7). Etiologies of this condition is multifactorial and not fully understood, yet some causes may be small bladder capacity, chronic constipation, genetic influences (autosomal dominant), delayed acquisition of urination control, de-trusor muscle malfunction, involuntary contractions, effect of psychological and behavioral factors, and delayed functional maturation of the central nervous system (8). Treating any underlying organic causes of enuresis is the first step of treatment (9,10).…”
Section: Introductionmentioning
confidence: 99%